1979
DOI: 10.1111/j.1432-1033.1979.tb13157.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Succinylated Wheat‐Germ Agglutinin

Abstract: The physicochemical and binding properties of succinylated wheat germ agglutinin are described in comparison with these of unmodified wheat germ agglutinin. Succinylated wheat germ agglutinin is an acidic protein with a p l of 4.0 0.2 while the native lectin is basic, p l of 8.5. The solubility of succinylated wheat germ agglutinin is about 100 times higher than that of the unmodified lectin at neutral pH. Both lectins are dimeric at pH down to 5, and the dissociation occurs at pH lower than 4.5. The binding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 21 publications
4
87
0
1
Order By: Relevance
“…These results demonstrate that S33D had been modified by glycosyltransferases of the trans-Golgi cisternae and the TGN and suggest that it is localized to the trans-Golgi cisternae and/or TGN . WGA binds both sialic acid and N-acetylglucosamine while succinylated WGA (sWGA) binds only N-acetylglucosamine (Monsigny et al, 1979(Monsigny et al, , 1980 . The binding of 110-kD S33D to WGA but not sWGA not only confirmed the presence of sialic acid on the N-linked glycans but also demonstrated that no N-acetylglucosamine residues were exposed on the glycans .…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that S33D had been modified by glycosyltransferases of the trans-Golgi cisternae and the TGN and suggest that it is localized to the trans-Golgi cisternae and/or TGN . WGA binds both sialic acid and N-acetylglucosamine while succinylated WGA (sWGA) binds only N-acetylglucosamine (Monsigny et al, 1979(Monsigny et al, , 1980 . The binding of 110-kD S33D to WGA but not sWGA not only confirmed the presence of sialic acid on the N-linked glycans but also demonstrated that no N-acetylglucosamine residues were exposed on the glycans .…”
Section: Resultsmentioning
confidence: 99%
“…Wheatgerm agglutinin (WGA, specific for sialic acid and GlcNAc), Concanavalin A (ConA, specific for α-D-mannose and α-D-glucose), and phytohaemagglutinin L (PHA-L, specific for the β1-6 branch at the trimannosyl core of N-linked carbohydrate) were obtained from Sigma Chemicals. Succinyl-WGA (succWGA, specific only for GlcNAc but not for sialic acid (Monsigny et al, 1979)) was purchased from Wheatgerm agglutinin-mediated toxicity in pancreatic cancer cells Vector Laboratories. Control lectins for sialic acid binding were Maackia amurensis agglutinin (MAA), Sambucus nigra agglutinin (SNA) and Limulus polyphemus agglutinin (LPA), all purchased from Sigma Chemicals.…”
Section: Lectinsmentioning
confidence: 99%
“…Some batches of WGA were modified by suecinylation (13) and/or conjugated to tetramethylrhodamine isothiocyanate (6). Lectin solutions were made fresh each day and stored at 0*C.…”
Section: Gamete Isolation and Handling: Gametes Of S Purpuratusmentioning
confidence: 99%